The Second Language Acquisition by Mixed Marriage Child (A Study Case) - Ann Pulsa, Luh (Humanis; Vol 22 No 3 (2018), 2018)
Unlike a general family, mixed marriage child has to learn other language starting from young age, or can be said as a bilingual child. He or she will learn their second language either his mother’s language or father’s language. The aims of this study are to find out the type of second language acquisition by the mixed marriage child and to find out the influencing factor for the child to acquire their second language . Three methods and technique are used in this study, the first is method and technique of collecting data using interview and recording methods in order to collect the data; the second is method and technique of analyzing data, qualitative method is used in this part by using three theories proposed by Ellis, Krashen Berry and Einsenson; and the third is method and technique of presenting data using informal method. The result of the study is Henry as mixed marriage child has naturalistic type who acquires the language by communicating with his family and surrounding directly. There are five factors influencing his second language acquisition; they are physiological condition and motor ability, intelligence, economic status, sex, and environment.